Characterization of a Tetrameric Inositol Monophosphatase from the Hyperthermophilic Bacterium Thermotoga maritima - Chen, Liangjing (American Society for Microbiology, 1999)
Inositol monophosphatase (I-1-Pase) catalyzes the dephosphorylation step in the de novo biosynthetic pathway of inositol and is crucial for all inositol-dependent processes. An extremely heat-stable tetrameric form of I-1-Pase from the hyperthermophilic bacterium Thermotoga maritima was overexpressed in Escherichia coli. In addition to its different quaternary structure (all other known I-1-Pases are dimers), this enzyme displayed a 20-fold higher rate of hydrolysis of d-inositol 1-phosphate than of the l isomer. The homogeneous recombinant T. maritima I-1-Pase (containing 256 amino acids with a subunit molecular mass of 28 kDa) possessed an unusually high V(max) (442 μmol min(−1) mg(−1)) that was much higher than the V(max) of the same enzyme from another hyperthermophile, Methanococcus jannaschii. Although T. maritima is a eubacterium, its I-1-Pase is more similar to archaeal I-1-Pases than to the other known bacterial or mammalian I-1-Pases with respect to substrate specificity, Li(+) inhibition, inhibition by high Mg(2+) concentrations, metal ion activation, heat stability, and activation energy. Possible reasons for the observed kinetic differences are discussed based on an active site sequence alignment of the human and T. maritima I-1-Pases.